SYNTHESIS OF ETHYLENEDIAMIDE FROM METHYL ESTER OIL ARABICA COFFEE SEEDS (Coffea arabica. L) WITH ETHYLENEDIAMINE USING NaOCH3 CATALYST BY AMIDATION REACTION - Maimunah, Siti; -, Daniel; Saleh, Chairul (Jurusan Kimia FMIPA UNMUL, 2020)
Synthesis of ethylenediamide surfactant from coffee bean oil methyl ester (Coffea arabica. L) through an amidation reaction. The synthesis process that has been carried out includes extraction, esterification and amidation of coffee bean oil content by soxhletation of 15.47% with acid number 3.15 mg KOH/g and ALB 1.58%. Coffee bean oil is converted to methyl ester through esterification and acid number is 1.50 mg KOH/g ALB level drops to 0.75% saponification number of 57.11 mg KOH / g. The most dominant composition of the coffee bean oil methyl ester based on GC-MS analysis was 48.0% methyl oleate. The FT-IR spectrum of methyl ester gives a specific absorption peak C = O ester at wave number 1745 cm-1. Methyl esters are converted to ethylenediamide through an amidation process. The resulting ethylenediamide has an acid number of 9.1 mg KOH/g and a saponification number of 3.39 mg KOH/g. The FT-IR spectrum provides specific absorption peaks for groups C=O at wave number 1639 cm1 and C-N at wave number 3302 cm-1. Ethylenediamide HLB values ​​are practically 12.5495 which includes oil in water (O/W) emulsifier surfactants.